PENGARUH STORE IMAGE, ONLINE CUSTOMER REVIEW DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi pada Mahasiswa UIN Sunan Ampel Surabaya) - EKA VIRAWATI; ANDRIANI SAMSURI (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2020)
used was quantitative with probability sampling with a sample selection technique taken randomly as many as 200 students of UIN Sunan Ampel Surabaya who become consumers or users of the Shopee marketplace. The analytical method was the T test, the coefficient of determination and path analysis. The results of this study indicated that partially / individually variable store images, online customer reviews and promotions had a significant effect on purchasing decisions at the Shopee marketplace. Therefore the store image variable, online customer reviews and promotions through purchase intention also had a positive and significant influence on purchasing decisions at the Shopee marketplace.